The police perspective towards the factors that influence people to involve in drug mule: A case study at Ibu Pejabat Kontijen Melaka / Norlaily Zainudin and Siti Murni Mohd Ali - Zainudin, Norlaily; Mohd Ali, Siti Murni (Faculty of Administrative Science and Policy Studies, 2013)
This research is about a study on factors that influence people to involve in drug mule: A case study In IPK Melaka. The researchers used judgment sampling techniques of 47 respondents of police officers at Ibu Pejabat Polis Kontinjen Melaka were answered questionnaire given. The objective of this research is to determine the relationship between factors and people involvement in drug mule. There are three factors that influence people to involve in drug mule which are money, family’s influence, and peer’s influence. These factors as independent variable while people involvement in drug mule as dependent variable on this study. The all factors have association significant relationship with people involvement in drug mule. This is due to result of chi-square that has been used. The most factors that influence people to involve in drug mule are peer’s influence followed by money and family’s influence. In conclusion, peer’s influence, money, and family’s influence can influence people to involve in drug mule.